Increased performance in elite runners following individualized timing of sodium bicarbonate supplementation - Lassen, T. A. H.; Lindstrøm, L.; Lønbro, S.; Madsen, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2021)
The present study investigated individualized sodium bicarbonate (NaHCO3-) supplementation in elite orienteers and its effects on alkalosis and performance in a simulated sprint orienteering competition. Twenty-one Danish male and female elite orienteers (age = 25.2 ± 3.6 years, height = 176.4 ± 10.9 cm, body mass = 66.6 ± 7.9 kg) were tested twice in order to identify individual time to peak blood bicarbonate (HCO3- peak) following supplementation of 0.3 g/kg body mass NaHCO3 with and without warm-up. The athletes also performed two 3.5 km time-trial runs (TT-runs) following individualized timing of NaHCO3 supplementation (SBS) or placebo (PLA) on separate days in a randomized, double-blind, cross-over design. The occurrence of individual peak HCO3- and pH ranged from 60 to 180 min. Mean HCO3- and pH in SBS were significantly higher compared with PLA 10 min before and following the TT-run (p < .01). SBS improved overall performance in the 3.5 km TT-run by 6 s compared with PLA (775.5 ± 16.2 s vs. 781.4 ± 16.1 s, respectively; p < .05). SBS improved performance in the last half of the TT-run compared with PLA (p < .01). In conclusion, supplementation with NaHCO3 followed by warm-up resulted in individualized alkalosis peaks ranging from 60 to 180 min. Individualized timing of SBS in elite orienteers induced significant alkalosis before and after a 3.5 km TT and improved overall performance time by 6 s, which occurred in the last half of the time trial. The present data show that the anaerobic buffer system is important for performance in these types of endurance events lasting 12-15 min.